The Obesity Paradox Is Not Observed in Critically Ill Patients on Early Enteral Nutrition*. Issue 5 (May 2017) - Harris, Kimberley; Zhou, Jiachen; Liu, Xinggang; Hassan, Erkan; Badawi, Omar
Abstract : Objectives: To investigate the association between body mass index and mortality in a large, ICU population and determine if the relationship is observed among a subgroup of patients ordered early enteral nutrition. Design: Retrospective cohort study within a national clinical mixed ICU database of patients admitted between January 1, 2008, and June 30, 2015. Setting: Initial ICU admissions among patients monitored by tele-ICU programs and recorded in the Philips e ICU Research Institute database. Patients: A total of 1, 042, 710 adult patient stays with ICU length of stay more than 24 hours, of which 74, 771 were ordered enteral nutrition within the first 48 hours. Intervention: None. Measurements and Main Results: Patient stays from 409 ICUs were included. The average age, Acute Physiology and Chronic Health Evaluation IV score, and hospital mortality were 63.6 years, 56.7, and 9.0%, respectively. Hospital mortality among body mass index categories was estimated by multivariable modified Poisson regression models. Compared with the body mass index category 25.0–29.9 kg/m 2, hospital mortality was higher among underweight (body mass index, < 18.5; relative risk, 1.35; 95% CI, 1.32–1.39), normal weight (body mass index, 18.5–24.9; relative risk, 1.10; 95% CI, 1.09–1.12), and the extremely obese (body mass index, ≥ 50.0; relative risk, 1.10; 95% CI, 1.05–1.15). However, the risk was not statistically different from patients with body mass index 30.0–49.9 kg/m 2 . Among patients ordered early enteral nutrition, the risk of mortality in the body mass index category 25.0–29.9 kg/m 2 was not statistically different from those in the normal weight or extremely obese groups. Conclusions: A survival advantage for overweight and obese patients was observed in this large cohort of critically ill patients. However, among those ordered early enteral nutrition, the survival disadvantage for body mass index categories less than 25.0 kg/m 2 was minimal or unobservable when compared with higher body mass index categories. Abstract : Supplemental Digital Content is available in the text.